Design of PBL-STEM E-Worksheet with Differentiated Instruction on Basic Chemical Laws to Improve Learning - Anggreini, Lia; Haryani, Sri (Chemistry in Education, 2025)
Science, Technology, Engineering, and Mathematics (STEM) education has been demonstrated to effectively enhance the quality of learning. However, the implementation of PBL-STEM in chemistry instruction, particularly on the topic of basic chemical laws, has not been optimally applied. This study aims to analyze the feasibility, effectiveness, and students’ responses toward the use of an electronic student worksheet (E-LKPD). The research employed a Research and Development (R&D) methodology using the 4D model, which includes the stages of Define, Design, Develop, and Disseminate. The subjects consisted of 33 tenth-grade students at SMA N 3 Semarang. Data analysis focused on the feasibility, effectiveness, and student feedback. The findings revealed that the PBL-STEM E-LKPD product was deemed valid by both content and media experts, indicating its suitability for educational use. The effectiveness of the E-LKPD was supported by an average N-gain score categorized as moderately effective. Significant improvements in N-gain scores were observed from pretest to posttest across all student groups. These results confirm that the integration of PBL-STEM E-LKPD with differentiated instruction is effective in improving students’ learning outcomes. Furthermore, positive student responses during the implementation of the E-LKPD in classroom settings reinforce its educational value.